Salmonella enterica Effectors SifA, SpvB, SseF, SseJ, and SteA Contribute to Type III Secretion System 1-Independent Inflammation in a Streptomycin-Pretreated Mouse Model of Colitis - Matsuda, Shigeki (Infect Immun, 2019)
Salmonella enterica serovar Typhimurium (S. Typhimurium) induces inflammatory changes in the ceca of streptomycin-pretreated mice. In this mouse model of colitis, the type III secretion system 1 (T3SS-1) has been shown to induce rapid inflammatory change in the cecum at early points, 10 to 24 h after infection. Five proteins, SipA, SopA, SopB, SopD, and SopE2, have been identified as effectors involved in eliciting intestinal inflammation within this time range. In contrast, a T3SS-1-deficient strain was shown to exhibit inflammatory changes in the cecum at 72 to 120 h postinfection. However, the effectors eliciting T3SS-1-independent inflammation remain to be clarified. In this study, we focused on two T3SS-2 phenotypes, macrophage proliferation and cytotoxicity, to identify the T3SS-2 effectors involved in T3SS-1-independent inflammation. We identified a mutant strain that could not induce cytotoxicity in a macrophage-like cell line and that reduced intestinal inflammation in streptomycin-pretreated mice. We also identified five T3SS-2 effectors, SifA, SpvB, SseF, SseJ, and SteA, associated with T3SS-1-independent macrophage cytotoxicity. We then constructed a strain lacking T3SS-1 and all the five T3SS-2 effectors, termed T1S5. The S. Typhimurium T1S5 strain significantly reduced cytotoxicity in macrophages in the same manner as a mutant invA spiB strain (T1T2). Finally, the T1S5 strain elicited no inflammatory changes in the ceca of streptomycin-pretreated mice. We conclude that these five T3SS-2 effectors contribute to T3SS-1-independent inflammation.